Incorrect Assumption: Transgender Men Do Not Willingly Engage in Vaginal Penetration. (1st August 2022) - Reginald-Okoli, C; Mula, M; Bachmann, G; Hutchinson-Colas, J
ABSTRACT: Introduction: In Western countries, biological sex is the organizing principle on which gender is constructed. Gender is commonly understood as innate-at birth, and upon genital inspection, a designation of "male" or "female" is given to the child and the presumed gendered characteristics and behaviors, including future sexual behaviors, are expected to follow. Transgendered individuals, who may perform societal normative gender scripts but do not possess the sexual anatomy of their gender identity, subvert the rigid boundaries of sexual dimorphism. For the healthcare community, the sexual behavior of transmen should be assessed, especially as it has pregnancy and STI implications. Objective: Because there are still several misconceptions about transgender men regarding preferred sexual practices and gratification, this research explored their sexual preferences, including engagement in vaginal penetration. The study examined the incorrect assumption of transgender men's disdain for a retained vagina and the idealization of masculinity as the ability to sexually "penetrate" their partner. It also analyzed whether the reconfiguration of gender identity by virtue of being a transgender man has any influence on the reconfiguration of sexual practice–more importantly, whether or not transmen engage and derive sexual pleasure from vaginal penetration. Methods: A literature review was conducted on sexual function in transgender men with a specific focus on vaginal penetration during sexual activity. PubMed/Medline and Google Scholar were used with keyword combinations that included, "transgender men", "transmen", "sexual function", "vaginal penetration", and "sexual pleasure". Results: The data suggested that subsets of transgender men do partake and derive pleasure from vaginal penetration. Outward perceptions of masculinity and gender validation from sexual partners were determined to be an important indicator of interest in vaginal penetration. For transgender men, there tended to be a reliance on gendered behavior, including sexual behavior, when their biological sex was perceived as being more outwardly ambiguous. An increase in perceived male identity as well as the establishment of secondary male sex characteristics correlated with an increase in the fluidity of sexual behavior, such as the touching of breasts, and vaginal intercourse. Many transgender men use language to recode bodies and sexual acts, such as referring to the clitoris as a penis, and the breast as a chest. By reclassifying the vagina from a female sex organ to a neutral front hole, transmen can engage in vaginal sexual intercourse without destabilizing their masculine embodiment. The literature also noted that for queer, bisexual, and gay transgender men being vaginally penetrated by cis-gendered men may re-affirm their male identity. Conclusions: Reframing gender and sexual behavior as dynamic and adaptable opens up a realm of possibilities for trans-identities. In this framework, sexual encounters and practices, which may or may not involve sexual organs misaligned with a transgendered individual's identity, have no bearing on their gender identity. The study findings highlight that transgender men often find pleasure in vaginally penetrative intercourse, and that there is less of a dependence on heteronormative sexual scripts as the female-to-male transition progresses. Disclosure: No